2022
DOI: 10.1002/lno.12061
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary DNA identifies modern and past macrophyte diversity and its environmental drivers in high‐latitude and high‐elevation lakes in Siberia and China

Abstract: Arctic and alpine aquatic ecosystems are changing rapidly under recent global warming, threatening water resources by diminishing trophic status and changing biotic composition. Macrophytes play a key role in the ecology of freshwaters and we need to improve our understanding of long‐term macrophytes diversity and environmental change so far limited by the sporadic presence of macrofossils in sediments. In our study, we applied metabarcoding using the trnL P6 loop marker to retrieve macrophyte richness and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Moreover, Alsos et al (2018) demonstrated that lake sediment eDNA from recent samples largely matches the extant vegetation with 88% of dominant and common taxa and 60% of rare taxa detected, and additionally records taxa missing in the survey that are likely true positives such as plants growing in deep water. Detection is also highly related to environmental conditions, especially temperature and water conductivity (Stoof-Leichsenring et al, 2022). Macrophyte communities constitute a good indicator of environmental conditions, especially in regions with high aquatic plant diversity which allows sensitivity to the spatial heterogeneity of the ecosystem, and can distinguish land use in river sections (Ji et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, Alsos et al (2018) demonstrated that lake sediment eDNA from recent samples largely matches the extant vegetation with 88% of dominant and common taxa and 60% of rare taxa detected, and additionally records taxa missing in the survey that are likely true positives such as plants growing in deep water. Detection is also highly related to environmental conditions, especially temperature and water conductivity (Stoof-Leichsenring et al, 2022). Macrophyte communities constitute a good indicator of environmental conditions, especially in regions with high aquatic plant diversity which allows sensitivity to the spatial heterogeneity of the ecosystem, and can distinguish land use in river sections (Ji et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In sum, macrophyte-based P6 loop metabarcoding supports reconstructions for a wide array of important freshwater metrics. From sed aDNA-derived macrophyte turnover and community composition, we can infer lake level changes (Heinecke et al, 2017) and conductivity and temperature changes (Stoof-Leichsenring et al, 2022) on millennial time scales. Our study extends environmental reconstructions for northern Fennoscandian lakes over the last twelve thousand years to thermal range, continentality, nutrient availability, light conditions, and water pH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A pronounced change from emergent to submerged taxa combined with an increase in macrophyte richness in Lake Naleng is found at 14 ka BP. Based on the modern results described above, this important turnover could be explained by an increase in temperature and water conductivity due to glacial runoff and high evaporation during the deglaciation (Stoof-Leichsenring et al, 2022).…”
Section: Plant Dna Metabarcoding Reveals Past Vegetation and Plant Di...mentioning
confidence: 97%